Antimycobacterial Activity of Newbouldia laevis Root and Stem Bark Extracts: In Vitro Evaluation and Phytochemical Composition - Zarto, Saleem Sule; Abdul, Sa'ad Sabri; Kpesibe, Joseph F.; Barau, Saminu Hamman (African Journal of Biochemistry and Molecular Biology Research, 2024)
This present study aimed to determine the phytochemical screening, antimicrobial and anti-tuberculosis activity of the root and stem bark of methanol extracts of the N. laevis plant from Gashaka Gumti national park of Taraba state. Phytochemical screening was carried out using standard methods. For the two extracts obtained from the root and stem bark which revealed the presence of all except cardiac glycosides and quinones in the root, while all were the stem bark extracts. The Anti-bacterial assay was carried out using Agar-well diffusion technique. The highest zone of inhibition for the root crude extract of E. coli was (18mm) and its lowest zone of inhibition was (2mm), the highest zone of inhibition of Stap. A was (22mm) and the lowest was (8mm), the highest zone of inhibition of Bacillus cereus (22mm) and its lowest was (10mm). Salmonella typhii had the highest zone of inhibition for the root extract at (24mm) and its lowest at (4mm). The highest zone of inhibition for stem bark crude extract of E. coli was (12mm) and its lowest zone of inhibition was (5mm), the highest zone of inhibition of Stap. A was (13mm) and the lowest was (6mm), the highest zone of inhibition of Salmonella typhii was (18mm) and its lowest was (18mm),the highest zone of inhibition of Bacillus cereus (12mm) and its lowest was (4mm). The anti- tuberculosis assay was carried out using Broth micro dilution method. The result concerning the mycobacterium TB (anti-tuberculosis) of the root and stem bark crude extract of N. laevis plants inhibit the growth of bacterium with inhibitory zone within the range 6-16mm. This study reveals that the methanolic crude extract of N. laevis root and stembark can be utilized as a potential anti-tuberculosis (TB) drug for novel discovery.